Faktor-faktor yang berhubungan dengan pelaksanaan integrasi layanan tb-hiv di puskesmas - Rosiana Putri; Rumita Ena Sari; Muhammad Rifqi Azhary; Arnild Augina Mekarisce (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2026)
Background: Tuberculosis (TB) and Human Immunodeficiency Virus (HIV) continue to be significant public health problems with high morbidity and mortality rates (WHO, 2023). Integrating TB-HIV services in primary health care facilities is crucial to improve early detection, treatment continuity, and quality of care (WHO, 2021). However, the implementation of integrated TB-HIV services in community health centers (Puskesmas) still faces various managerial challenges. Purpose: This study aims to identify factors associated with the implementation of integrated TB-HIV services in community health centers (Puskesmas). Method: This quantitative analytical study used a cross-sectional approach. This study was conducted in 20 community health centers in Jambi City from January to March 2026. The sample consisted of 60 health workers selected through a total sampling technique. Data were collected using a validated questionnaire with good reliability. Univariate analysis was conducted to describe the distribution of variables, while bivariate analysis used the Chi-Square test with a 95% significance level and the Fisher exact test. Results: Planning had a significant relationship with the implementation of TB-HIV service integration (p-value = 0.019; PR = 4.50), implementation also had a significant relationship (p-value = 0.019; PR = 4.50), and control also showed a significant relationship (p-value = 0.004; PR = 5.57). Meanwhile, organization did not show a significant relationship with the implementation of TB-HIV service integration (p-value = 0.356). Conclusion: Planning, implementation, and supervision are closely related to the implementation of TB-HIV service integration in community health centers.   Keywords: Actuating; Controlling; Organizing; Planning,Public Health Center; TB-HIV Integration.